Application of GIS tools in spatial distribution modeling of historical monuments - Rząsa, Krzysztof; Ciski, Mateusz; Ogryzek, Marek (Geomatics and Environmental Engineering, 2019)
Entry in the register of objects of cultural heritage (Polish: rejestr zabytków) is one of the statutory forms of legal protection of monuments in Poland. The registers of objects of cultural heritage are maintained by territorially competent voivodeship conservators of monuments. Voivodeship registers of objects of cultural heritage contain approx. 76,000 entries related to non-movable monuments that are differentiated by type. These objects can be cultural landscapes, urban and rural systems, construction units, works of architecture and con-struction, defensive structures, monuments of technology, cemeteries, parks, gardens, and other forms of designed greenery as well as places that commemorate historical events or the activities of outstanding figures on institutions.In this paper, research was conducted on the possibilities of using GIS tools in analyses regarding the spatial distribution of historical monuments in Poland. Data from the National Heritage Board of Poland (Polish: Narodowy Instytut Dziedzictwa) obtained from the dane.gov.pl website was analyzed. Maps showing the density of non-movable monuments specifying their types and locations were created. Warmian-Masurian Voivodeship was an area of detailed research. The generated maps can be used for creating and updating the national spatial development concept (Polish: koncepcja przestrzennego zagospodarowania kraju) as well as voivodeship spatial management plans.